2012
DOI: 10.1038/onc.2012.13
|View full text |Cite
|
Sign up to set email alerts
|

Switching from aerobic glycolysis to oxidative phosphorylation modulates the sensitivity of mantle cell lymphoma cells to TRAIL

Abstract: TRAIL (TNF (tumour necrosis factor)-related apoptosis-inducing ligand) a putative anti-cancer cytokine induces apoptosis through DISC (death-inducing signalling complex)-mediated activation of caspase-8 and/or cleavage of Bid. TRAIL is relatively specific for tumour cells but primary chronic lymphocytic leukaemia and mantle cell lymphoma (MCL) cells are resistant. Herein, we show that cellular metabolism influences cell death and that MCL cells (Z138 cell line) can survive/proliferate in glucose-free media by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 51 publications
(43 reference statements)
6
73
1
1
Order By: Relevance
“…However, it seems unlikely that the diversity of the metabolomes, extending over 43 essential genes in three prostate cancer cell lines, can be explained by the status of PTEN Given this metabolic flexibility, even if an efficacious target for a cancer patient can be found, might the cancer just elude a metabolic inhibitor-based therapy by altering its own metabolism? This has been shown in an established cell line by Robinson and colleagues [9]. Z138 mantel lymphoma cells incubated in glucose-depleted media supplemented with pyruvate and glutamine easily survived the adverse conditions by switching to aerobic respiration.…”
mentioning
confidence: 75%
“…However, it seems unlikely that the diversity of the metabolomes, extending over 43 essential genes in three prostate cancer cell lines, can be explained by the status of PTEN Given this metabolic flexibility, even if an efficacious target for a cancer patient can be found, might the cancer just elude a metabolic inhibitor-based therapy by altering its own metabolism? This has been shown in an established cell line by Robinson and colleagues [9]. Z138 mantel lymphoma cells incubated in glucose-depleted media supplemented with pyruvate and glutamine easily survived the adverse conditions by switching to aerobic respiration.…”
mentioning
confidence: 75%
“…After entering the cell, 2DG is phosphorylated by HK to form 2-Deoxy-D-glucose-6-phosphate (2DG-6-P), which cannot be further metabolized via glycolysis but accumulates and noncompetitively inhibits HK and competitively inhibits PGI [7,38,43]. Because 2DG inhibits the first critical steps at the beginning of glucose metabolism, both glycolysis and OXPHOS may be partially disrupted [44]. These events lead to decreased ATP production, blocked cell cycle, decreased and inhibited cell growth and even cell death [6,16,40].…”
Section: Inhibition Of Glycolysis and Depletion Of Atpmentioning
confidence: 99%
“…In our study, a higher lactate/alanine ratio was observed in the high-dosage group (30.3 ± 5.8 vs 13.4 ± 8.8 of control, p \ 0.01) at 6 h post-treatment of silica nanoparticles, which indicated a higher reductive/lower oxidative state of the HeLa cells. The reduced ATP in our study may be related to oxidative phosphorylation in mitochondria (Robinson et al 2012 which was promoted by the activation of transcription factor-2 (ATF-2) (Mohamed et al 2011), a member of the basic transcription factor family that regulates the expression of genes in response to various stress signals (Gupta et al 1995). However, such conclusion needs to be further tested in the possible animal experiment.…”
Section: Nmr Profile Of Hela Cells and Corresponding Culture Mediamentioning
confidence: 89%